National Strategic Plan for Excellent Centers of Medical Service and Academic and Research in Thailand (5-10 years) - พอกเพิ่มดี พงศธร (Journal of Health Science of Thailand, 2020)
In the year 2014, National Councils for Peace and Order assigned Ministry of Public Health, Ministry of Education and Office of the National Economics and Social Development Councils to develop the national strategic plan for Excellent Centers of Medial Service, academic and research in Thailand (5- 10 years), corresponding with changing of economics, social and environment in Thailand. This strategic plan has been developed by using the processes of the office of the public sector development commission with the involving of stakeholders. This processes consist of (1) strategic analysis, (2) strategic direction and setting, (3) strategic formulation, and (4) strategic implementation. The vision of this strategic plan is “Thailand is the center of medical excellent in the region” and the vision is (1) develop capacity of competitive growth, (2) expanding coverage of excellent centers through the regions, and (3) develop international medical education institute and 4) develop capacity of medical research and innovation in Thailand. The objectives of this strategic plan are to be excellent in 3 areas including (1) medical service, (2) academic, and (3) research, by deploying 3 strategies: (1) competitive advantages, (2) health system strengthening, and (3) disparity of health system rendering.